Scale-up fabrication and characteristic study of oligomer-like small-molecule solar cells by ambient halogen-free sheet-to-sheet and roll-to-roll slot-die coating. (1st January 2022) - Sung, Yun-Ming; Tsao, Cheng-Si; Lin, Hua-Kai; Cha, Hou-Chin; Huang, Yu-Ching
Highlights: Halogen-free and ambient slot-die coating of the small-molecule organic solar cell and module. Thermal annealing for mass production, good photo-stability and indoor lighting performance. Tunable BHJ film morphologies of sheet-to-sheet and flexible roll-to-roll slot-die coatings. Efficiency of S2S and flexible R2R slot-died SMOSC achieve 7.6% and 7.3%, respectively, Characteristic, structural and systematic study correlating processing and performance. Abstract: The upscale fabrication of the inverted small-molecule organic solar cell (SMOSC) from spin coating to large-area slot-die coating using halogen-free solvent under the ambient air environment is developed. This work successfully adopts thermal annealing treatment to tune the bulk heterojunction (BHJ) structure for two advantages of compatibility to mass production and good photo-stability. By tuning the respective optimum film structure, the power conversion efficiency (PCE) values under AM 1.5G light and indoor light (T5 lamp with 500 lx) illuminations for the ambient spin-coated device achieve 8.5% and 13.26%, respectively. The photo-bleaching and light-soaking tests under the AM 1.5G illumination show that the photo-stability of the thermally-annealed DRCN5T:PC71 BM device is much better than PTB7-Th:PC71 BM device. The tunable BHJ film morphologies of large-area ITO/glass-based sheet-to-sheet (S2S) and flexible roll-to-roll (R2R) slot-die coatings of DRCN5T:PC71 BM SMOSCs are based on different dry-film formation and crystallization mechanisms. The structural control during the drying-film process for S2S and R2R coatings is a critical key to determine the optimum performance. The PCEs of the ITO/glass-based and flexible ITO/PET-based SMOSCs achieve 7.6% and 7.3%, respectively. The PCE of the ambient flexible R2R slot-die-coated SMOSC using halogen-free solvent is much higher than that of the currently flexible R2R coated SMOSCs. The PCEs of S2S slot-die-coated cell device of 1 × 5 cm 2 and module achieve 5.1%. We conduct a characteristic, structural and systematic study of how to scale-up SMOSC via slot-die coatings, demonstrating the relationship among processing control, performance and structure for different coatings.